Fostering Scientific Reasoning and Understanding: Developing Jumping Task-Based Learning Materials for the Solar System Topic in Primary Education - M. Fikra Yusuf Annazar; Elsa Aprianisa; Gina Zahra; Apriliana Puspa Andhani (Journal of Adaptive Education, 2025)
Development of Jumping Task-Based Lkpd to Improve Student Achievement of Learning Outcomes. This study aims to develop Jumping Task-based worksheets that can be used to improve student achievement. This research is a research and development research and development (R&D) using the ADDIE research model. Collecting data using the method of observation, interviews, and questionnaires. Observations were made during the analysis of the school environment. Interviews are needed to determine the needs of teachers, students, and problems in the learning process. Questionnaires were used to assess the validity of the LKPD from the aspect of material, media, use of LKPD, and implementation of learning, and were used in trials to students to measure the feasibility of LKPD based on Jumping Task. The subjects of this study were 46 students of class VI. This research produces LKPD based on Jumping Task in the solar system science subjects. The results showed the average pretest 69,71 and the average posttest 79,49. The results of the calculation of the achievement of affective aspects obtained the final value of class VIA, namely 87.92 with very high criteria, class VIB getting a score of 85,46 with very high criteria. While the results of the calculation of the achievement of psychomotor aspects at the end of class IVA, namely 86,25 with very high criteria, class VIB got a score of 82,08 with very high criteria. So it can be concluded that the developed LKPD can improve student achievement.